Enya (Atlantic, 1986)
Description Not Provided
The Celts (2:56) , Aldebaran (3:05) , I want tomorrow (4:00) , March of the Celts (3:15) , Deireadh an tuath (1:42) , The sun in the stream (2:54) , To go beyond (I) (1:19) , Fairytale (3:02) , Epona (1:35) , Triad (4:23). St. Patrick ; Cu Chulainn ; Oisin , Portrait (1:23) , Boadicea (3:30) , Bard dance (1:23) , Dan y dwr (1:41) , To go beyond (II) (2:58).

The very best of Enya (Reprise, 2009)
Description Not Provided
Orinoco flow , Aníron = I desire , Storms in Africa , Caribbean blue , Book of days , The Celts , Only time , Wild child , Water shows the hidden heart , Anywhere is , Cursum perficio , Amarantine , Aldebaran , Trains and winter rains , Watermark , Boadicea , A day without rain , May it be , Oíche chiúin / trad.

Dark Sky Island (Warner Bros, Warner Records, 2015)
Description Not Provided
The humming... , So I could find my way , Even in the shadows , The forge of the angels , Echoes in rain , I could never say goodbye , Dark sky island , Sancta Maria , Astra et luna , The Loxian gate , Diamonds on the water.

A Day Without Rain (WM UK, Reprise Records, 2005)
Description Not Provided
A day without rain , Wild child , Only time , Tempus vernum , Deora ar mo chroi , Flora's secret , Fallen embers , Silver inches , Pilgrim , One by one , The first of autumn , Lazy days.

Paint the sky with stars: the best of Enya (Warner Music, 1997)
Description Not Provided
Orinoco flow , Caribbean blue , Book of days , Anywhere is , Only if... , The Celts , China roses , Shepherd moons , Ebudae , Storms in Africa , Watermark , Paint the sky with stars , Marble halls , On my way home , Memory of trees , Boadicea.

Shepherd moons (Warner Music UK Ltd./Reprise Records, 1991)
Description Not Provided
Shepherd moon , Caribbean blue , How can I keep from singing? , Ebudae , Angeles , No holly for Miss Quinn , Book of days , Evacuee , Lothlorien , Marble halls , Afer Ventus , Smaointe ...